DA’WAH TO FARMERS AND FISHERMAN COMMUNITIES : (Study on the Kaili Etnic in Central Sulawesi) - Muhammad Najmuddin; Badruddin Kaddas (LTN NU Sulawesi Tengah, 2023)
This article discusses the role and strategies of da'wah in enhancing religious awareness and spiritual well-being among farmers and fishermen of the Kaili ethnic group. Through field studies and data collection methods such as interviews, observations, and literature reviews, this research explores how da'wah can address their religious and spiritual needs. The findings reveal that the Kaili farmers and fishermen heavily rely on agriculture and fishing as their primary livelihood. They have a strong connection with nature and their surrounding environment, uphold traditional values and customs, and exhibit high solidarity and communal spirit. However, they face challenges such as limited resources, unpredictable weather and seasons, economic difficulties, as well as geographical and social isolation. In this context, da'wah plays a crucial role in strengthening the faith and spiritual well-being of the Kaili community. Effective da'wah approaches encompass education and dissemination, social engagement, and technology-based initiatives. The implications of this research can serve as a guide for da'wah activists, government entities, and related organizations in developing relevant and impactful da'wah strategies for the farmers and fishermen, particularly within the context of the Kaili ethnic group.